Effect of graded doses of neem coated urea on productivity of low land rice - Pradhan, P P; Dash, A K; Panda, N; Samant, P K; Mishra, A P (ORYZA-An International Journal of Rice, 2019)
A field experiment was conducted in the Research field of Regional Research and Technology Transfer Station, Coastal Zone, OUAT to study the efficiency of neem coated urea (NCU) on yield and yield attributing characteristics of low land rice. Results revealed that application of 80 kg N ha-1 as NCU was effective overapplication of 100 kg N ha-1 as prilled urea (PU). The highest plant height (109.8 cm) panicle length (24 cm) and effective tiller (11.5) was observed with T5 (100 kg N ha-1 as PU) whereas lowest value of 84.5 cm, 20.6 cm and 9.1 cm for plant height, panicle length and effective tillers per hill respectively were recorded with T1 (control). The highest grain yield of 47.3 q ha-1 was observed in T8 (80 kg N ha-1 as NCU) where as lowest value of 32.7 q ha-1 was observed in T1 (control). The grain yield of rice under T5 (100 kg N ha-1 as PU) was 47.0 q ha-1 which was statistically at par with T8 (80 kg N ha-1 as NCU) indicating the higher efficiency of NCU than that of PU. With the doses at 80 kg N ha-1 the yield advantages was due to application of NCU which had a 5.1% more yield advantages than that of PU. The straw and harvest index followed the same trend as that of grain yield of rice. The highest B: C ratio of 1.44 was observed with application of 80 kg N ha-1 as NCU where as the B: C value of 1.42 was observed with application of 100 kg N ha-1 as PU indicating the efficiency of NCU than that of PU application.